Prevalence and risk factors of sleep apnoea in adult patients with CHD. (29th November 2018) - Harada, Gen; Takeuchi, Daiji; Inai, Kei; Shinohara, Tokuko; Nakanishi, Toshio
Abstract: Background: Although sleep apnoea is an important disorder associated with cardiac events, data regarding its prevalence and risk factors in adult patients with CHD are limited. Methods: In this study, patients underwent a sleep study in the hospital. Indications for admission were classified as heart failure, diagnostic catheterisation, interventional catheterisation, or arrhythmia. The prevalence, characteristics, and risk factors of sleep apnoea using a type 3 portable overnight polygraph in adult patients with CHD were evaluated. Results: This study comprised 104 patients of median age 36 years with interquartile range of 28–48 years, admitted for heart failure 34% (n = 36), diagnostic catheterisation 26% (n = 27), interventional catheterisation 18% (n = 19), or arrhythmia 22% (n = 23). The prevalence of sleep apnoea, defined as a respiratory disturbance index ≥5, was 63% (n = 63), with a distribution of 37, 16, and 10% for mild (5≤ respiratory disturbance index <15), moderate (15⩽ respiratory disturbance index <30), and severe (respiratory disturbance index ≥30) sleep apnoea, respectively. A large majority of the sleep apnoea cases were categorised as obstructive sleep apnoea (92%, n = 58). The respiratory disturbance index ≥15 group had a significantly higher proportion of male patients and higher body mass index, noradrenaline level, and aortic blood pressure than the group without sleep apnoea (respiratory disturbance index <5). Multi-variable analysis showed that NYHA class ≥II, whose odds ratio 4.36, 95% confidence interval 1.09–20.87, and body mass index ≥25, whose odds ratio 4.29, 95% confidence interval 1.32–15.23, were independent risk factors for a respiratory disturbance index ≥15. Conclusion: Our results showed a high prevalence of sleep apnoea in adult patients with CHD. Its unique haemodynamics may be associated with a high prevalence of sleep apnoea. Congestive heart failure and being overweight are important risk factors for sleep apnoea. Management of heart failure and general lifestyle improvements are important for controlling sleep apnoea symptoms in these patients.